Measurement of Saccade Parameters in Relation to Adaptation to Homonymous Hemianopia - Claire Howard; Paul Knox; Helen Griffiths; Fiona Rowe (British and Irish Orthoptic Journal, 2022)
Purpose: To report saccade parameters in participants during adaptation to post-stroke homonymous hemianopia. Methods: In a prospective observational case cohort study, adult stroke survivors with new onset homonymous hemianopia were recruited. Using quantitative measurement, saccade parameters were measured and compared between the hemianopic and non-hemianopic sides. Two participants with longitudinal measurements were compared with age-matched controls. Results: Of 144 clinical study participants, quantitative saccade measurements were only possible in 14 due to an inability to visualise targets on the hemianopic side in the majority. In 9 of the 14 participants, at four weeks post-stroke, mean (±SD) saccade latency was significantly longer to the hemianopic (328.4 ± 105.9 ms) compared to the non-hemianopic side (234.7 ± SD53.6 ms; 't' = 4.2, 'df' = 8, 'p' = 0.003). The number of correct saccadic responses out of 50 was significantly lower to the hemianopic side (36.6 ± SD14.1) in comparison to the non-hemianopic side (44.4 ± SD7.5; 't' = –3.1, 'df' = 8, 'p' = 0.014). In two participants studied over an eight-week time period, saccadic differences to the hemianopic side persisted despite apparent recovery of visual field. Conclusion: As participants with residual visual field loss were unable to perform quantitative assessments, the widespread use of this approach in this setting is limited. However, in those whom measurements were possible, there were statistically significant differences in saccade parameters between hemianopic and non-hemianopic sides that persisted post-visual recovery. Exploration of saccades in relation to adaptation to hemianopia and response to saccadic scanning/search training requires further examination.